Динамика вихрей Абрикосова на цилиндрических микротрубках; Известия вузов. Физика; Т. 58, № 5 - Резаев Р. О. Роман Олегович; Левченко Е. А. Евгений Анатольевич; Шмидт О. Оливер; Фомин В. М. Владимир Михайлович (2015, 2015)
Заглавие с экрана